Contribution of forestersin support of ecosystem structure of nature and all ocation agroecosystems - Migunova, E.S. (AgroChemistry and Soil Science, 2016)
There are described briefly the development of domestic foresters, the typology in the field of forest and environment linkages, given the definition of ecosystems and their classification. It is justified the expediency of division of agricultural land to agro-ecosystems like forest ecosystems, taking into account not only the types of soil, but also the nature of the parent material, topography, groundwater. Lands within agro-ecosystems should be characterized by a similar level of fertility.